PENINGKATAN KEMAMPUAN KOORDINASI MATA DAN TANGAN MELALUI PERMAINAN LEMPAR TANGKAP BOLA BAGI SISWA GANGGUAN SPEKTRUM AUTISME - Komalasari, Chece; Efrina, Elsa; Rahmahtrisilvia, Rahmahtrisilvia; Taufan, Johandri; Handayani, Endang Sri (STKIP Pesisir Selatan, 2025)
This study aimed to improve hand–eye coordination skills in students with Autism Spectrum Disorder (ASD) through the implementation of a ball throwing and catching game as a motor learning strategy at the foundational phase. The research was conducted at SLB Autis Bima Padang using a Classroom Action Research design consisting of two cycles, each comprising four instructional sessions. The research subjects were two students identified by the initials IN and GK. Data were collected through structured observation focusing on students’ hand–eye coordination performance during learning activities, while data analysis employed percentage techniques to identify improvements across cycles. The findings revealed a consistent increase in hand–eye coordination abilities in both students. The initial performance levels of students IN and GK were 39% and 44%, respectively. After the implementation of actions in Cycle I, the scores increased to 59% for IN and 61.10% for GK. Further improvement was observed in Cycle II, where IN reached 70.31% and GK achieved 72.21%. The novelty of this study lies in the use of a systematically and progressively modified ball throwing and catching game as a simple, practical, and developmentally appropriate motor learning intervention tailored to the characteristics of students with ASD at the foundational phase.